METODE ISOLASI YANG MUDAH DALAM ISOLASI SENYAWA β-KAROTEN DARI LABU KUNING (Cucurbita moschata Duch ex Poiret) - Rollando Rollando; Muhammad Hilmi Afthoni (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTPumpkin (Cucurbita moschata Duch ex Poiret), a fruit that contains several compounds, has activities to protect the human body from free radicals. Provitamin A is recognized as an antioxidant compound. Antioxidants can protect the body’s damage caused by free radicals. The purpose of this study was to isolate beta carotene compounds and test the purity of beta carotene isolates obtained using DR-UV and infrared spectrophotometry. Pumpkin is extracted using acetone: petroleum ether with a ratio (1: 1). Identification of beta carotene from extracts was carried out using TLC with the mobile phase of ethanol: acetone: n-hexane with a ratio (2: 1: 1) and scan spectrum using a UV-Vis spectrophotometer. Beta carotene was identified as the result of TLC elution on UV 254 and 366 nm which showed 2 spots. Detection of beta carotene spectra was carried out in the range of 350 to 550 nm and obtained beta carotene peaks at wavelength x nm. The extract purification process was carried out using Preparative TLC with the mobile phase of ethanol: acetone: n-hexane with a ratio (2: 1: 1) and obtained isolates cleaned first using chloroform: methanol ratio of 1: 1. The isolates were dried and tested using DR-UV and infrared spectrophotometry. Isolates from Cucurbita moschataDuch ex Poiret extract) contain beta carotene, zeaxanthin.Keywords: pumpkin; beta carotene; isolation